Introduction to the Special Issue: New Perspectives on Public and Social Rental Housing in the Nordic Countries, part two - Martin Grander; Jardar Sørvoll (Tidsskrift for boligforskning)
In this short introductory article, we summarise the contributions to the second part of the special issue on public and social rental housing in the Nordic countries. We also emphasise that the journal is happy to consider scientific papers for publication from across the Nordic region addressing the most pressing housing-related questions of the day. As inequality has been on the rise throughout the previously so egalitarian Nordics in recent decades, we strongly encourage researchers to submit papers that situate housing markets and housing policies in the wider debate and empirical research on inequality.